EFFECT OF FOLIAR SPRAY OF MICRONUTRIENTS ON FLOWERING AND FRUITING OF ALPHONSO MANGO (MANGIFERA INDICA L.) - TULSI D. GURJAR; N. L. PATEL; BHAKTI PANCHAL; DARSHANA CHAUDHARI (The Bioscan, 2015)
Alphonso has most of the quality merits but it has some serious inherited physiological disorders such as, alternate bearing habit and excessive/heavy fruit drop that occurs at different stages of fruit growth till harvest is considered as one of the long standing unresolved problems, directly and substantially contributing to its poor yield along with other problems. To overcome this problem the experiment was planned witheleven treatments involving two levels of micronutrients (ZnSO4 1% and 2%; FeSO4 1% and 2% and Borax 0.5% and 1%), their combinations and a control. Results revealed that foliar application of 1% ZnSO4, 1% FeSO4 and0.5% borax in combination had influenced flowering in terms of minimum days(19.67) taken to 50% flowering and increased length of panicle(40.33 cm) compared to other treatments and control. The treatment ZnSO4 1% + FeSO4 1% + borax 0.5% significantly increased the fruit set at pea stage (14.00) and marble stage (7.50), number of fruits per tree (1.73), average fruit weight (314.69 g) and yield per tree (185.09 kg) and decreased the fruit drop (87.66 %).